The ottomans disolving images - Wheatcroft, Andrew (Penguin Books, 1995)
The Ottoman Empire was a "mystery wrapped inside the enigma". This book aims to unravel the mystery in two ways. Firstly, it looks at the Ottomans and their world in terms relevant to an eastern Islamic society, with its own principles and practices that seemed merely barbaric to the West. The book also comes to terms with the West's expectations of the Ottomans. The author's aim is both to tell the story and offer some explanation. The book interprets the Ottomans, to make sense of a society that to Western eyes seemed feckless and utterly corrupt, cruel and craven by turns. It was frequently all of these things but not without reason or cause.